A method for reinforcing recycled aggregates for lightweight construction materials

CN122916487APending Publication Date: 2026-10-16ZHEJIANG DEHAO APPLIED ENG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611296885.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]但是,建筑垃圾再生骨料的来源组成复杂,不同批次中废弃混凝土块、废弃砂浆块和烧结砖瓦碎块的比例存在差异,颗粒表面附着旧砂浆层的面积占比、裂隙连通状态以及孔隙吸液能力并不一致

Benefits of technology

[0029] I. This invention collects the area ratio of the attached old mortar layer and the fissure connectivity of recycled aggregate from construction waste, and determines the treatment level of the old mortar layer accordingly. This allows subsequent reinforcement treatment to match the residual degree of the old mortar layer and the fissure connectivity of the recycled aggregate from construction waste, avoiding fluctuations in treatment results caused by using uniform treatment conditions for recycled aggregate from different sources and with different degrees of damage. This is beneficial to improving the batch consistency of reinforced recycled aggregate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916487A_ABST
    Figure CN122916487A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building waste resource utilization and recycled aggregate processing, and discloses a recycled aggregate reinforcing method for light building materials, which comprises the following steps: removing impurities, crushing, screening and warehousing of waste concrete blocks, waste mortar blocks and sintered brick and tile fragments in building waste to obtain to-be-reinforced recycled aggregate and prepare homologous recycled micro powder; collecting initial water absorption rate, initial crushing index, apparent density, attached old mortar layer area proportion and crack connectivity to determine the old mortar layer processing grade; obtaining reinforced recycled aggregate through calcium-containing inner hole pre-occupying liquid negative pressure introduction, surface layer liquid discharge, wet state rolling shell formation, intermittent carbon dioxide carbonization and re-measurement updating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of construction waste resource utilization and recycled aggregate processing technology, and in particular to a method for reinforcing lightweight building materials with recycled aggregate. Background Technology

[0002] Waste concrete blocks, waste mortar blocks, and sintered brick and tile fragments from construction waste can be used as recycled aggregates in lightweight building materials after impurity removal, crushing, and screening. These recycled aggregates originate from the demolition of existing buildings, structures, or renovations. Their particle surfaces typically retain a layer of old mortar, which contains pores, micro-cracks, and locally loose areas. Compared to natural aggregates, recycled construction waste aggregates usually exhibit higher water absorption, fluctuating apparent density, and unstable crushing indices, affecting batch consistency when used as aggregates in lightweight building materials.

[0003] Existing technologies already include methods for strengthening recycled aggregates from construction waste. For example, patent application CN105174766A discloses a method for strengthening recycled concrete fine aggregates using carbon dioxide. This method involves spreading recycled fine aggregates prepared from construction waste, spraying them with a calcium hydroxide solution or calcium salt solution, and stirring thoroughly. The treated recycled fine aggregates are then placed in a sealed carbonation chamber for carbon dioxide curing, thereby strengthening the recycled fine aggregates through a carbonation reaction. This type of method can carbonize the calcium-containing components in the mortar adhering to the surface of the recycled aggregates and is a relatively close existing technical solution for modifying recycled aggregates from construction waste.

[0004] However, the composition of recycled aggregates from construction waste is complex. The proportions of waste concrete blocks, waste mortar blocks, and sintered brick and tile fragments vary across different batches. The percentage of the surface area covered by the old mortar layer, the connectivity of cracks, and the liquid absorption capacity of the pores are also inconsistent. Existing calcium salt spraying and carbon dioxide carbonization treatments typically apply uniform treatment conditions to the entire batch of recycled aggregates, making it difficult to distinguish the degree of residual old mortar layer and crack connectivity differences between different particles or batches. Consequently, the treated recycled aggregates may still exhibit significant fluctuations in water absorption and crushing indices.

[0005] Therefore, the main technical problem that still needs to be solved in the reinforcement treatment of recycled construction waste aggregate as a lightweight building material is: how to adapt the reinforcement treatment of recycled construction waste aggregate to the differences in the adhesion degree and crack connectivity of the old mortar layer, achieve precise shelling and reinforcement based on differentiated grading, and reduce the continuous batch fluctuations of water absorption rate and crushing index of the treated recycled aggregate by combining dynamic detection. Summary of the Invention

[0006] In order to overcome the above-mentioned technical defects, the purpose of this invention is to provide a method for reinforcing lightweight building materials with recycled aggregates.

[0007] This invention discloses a method for reinforcing lightweight building materials with recycled aggregates, comprising the following steps:

[0008] S1. Remove impurities, crush, screen and separate waste concrete blocks, waste mortar blocks and sintered brick and tile fragments from construction waste to obtain recycled aggregate to be reinforced, and prepare homologous recycled micro powder from the separated construction waste particles.

[0009] S2. Collect the initial water absorption rate, initial crushing index, apparent density, area ratio of the attached old mortar layer, and fissure connectivity of the recycled aggregate to be reinforced, and determine the treatment level of the old mortar layer based on the area ratio of the attached old mortar layer and fissure connectivity.

[0010] S3. The calcium-containing pre-filled liquid is introduced into the recycled aggregate to be reinforced under negative pressure, and then the surface is drained to obtain pre-treated aggregate with calcium-containing pre-filled liquid in the pores and the area of ​​continuous liquid film on the surface is less than 5%.

[0011] S4. According to the treatment grade of the old mortar layer, calcium source filling liquid, homologous recycled micro powder and silicate shell liquid are added to the pretreated aggregate in sequence, and wet rolling shell is performed to obtain wet shell aggregate.

[0012] S5. Perform intermittent carbon dioxide carbonization treatment on wet shell aggregate for at least two carbonization cycles, and allow it to be rehydrated and allowed to stand between two adjacent carbonization cycles to obtain reinforced recycled aggregate.

[0013] S6. Retest the water absorption rate and crushing index of the reinforced recycled aggregate, and update the dosage of calcium source filling liquid, homologous recycled micro powder and silicate shell liquid for the next batch of reinforced recycled aggregate based on the retest results.

[0014] Preferably, in step S1, the construction waste is divided into a concrete source bin, a mortar source bin, and a brick and tile source bin, and the recycled aggregate particles to be reinforced and the particles for preparing homologous recycled micro powder are obtained from the concrete source bin, the mortar source bin, and the brick and tile source bin, respectively.

[0015] Preferably, in step S2, the fracture connectivity is determined by the fracture image after coloring and pre-wetting, and the fracture connectivity is the ratio of the length of the connected fracture to the total length of the fracture.

[0016] Preferably, in step S2, the treatment level of the old mortar layer includes a first-level treatment level, a second-level treatment level, and a third-level treatment level; when the area of ​​the attached old mortar layer is not less than 45% and the fissure connectivity is not less than 0.35, it is determined to be a first-level treatment level; when the area of ​​the attached old mortar layer is less than 25% and the fissure connectivity is less than 0.18, it is determined to be a third-level treatment level; and in other cases, it is determined to be a second-level treatment level.

[0017] Preferably, in step S3, the negative pressure introduction treatment of calcium-containing pore prefilling liquid includes placing the regenerated aggregate to be reinforced in the impregnation chamber, pumping the impregnation chamber to a negative pressure state and adding calcium-containing pore prefilling liquid, maintaining the negative pressure state and then restoring it to normal pressure state, and discharging the free calcium-containing pore prefilling liquid that has not entered the pores of the regenerated aggregate to be reinforced.

[0018] Preferably, in step S3, the surface drainage treatment includes rolling and blowing the recycled aggregate to be reinforced after the pre-filled calcium-containing pore liquid negative pressure introduction treatment is completed, and the area ratio of the continuous liquid film region on the surface is identified by the surface water content image.

[0019] Preferably, in step S4, the calcium source filling liquid is added in a segmented spraying manner, which includes a first spray, intermittent rolling, and a second spray. When the old mortar layer treatment level is Grade I, the amount of calcium source filling liquid used in the second spray is 40% to 70% of the amount used in the first spray. When the old mortar layer treatment level is Grade II, the amount of calcium source filling liquid used in the second spray is 15% to 35% of the amount used in the first spray. When the old mortar layer treatment level is Grade III, the second spray is omitted.

[0020] Preferably, in step S1, the homologous recycled micro powder is obtained by grinding and classifying the homologous recycled micro powder preparation particles. The homologous recycled micro powder includes old mortar micro powder with a particle size of no more than 75 μm and brick and tile micro powder with a particle size of no more than 45 μm. The old mortar micro powder and brick and tile micro powder are prepared according to the mass ratio of the corresponding recycled aggregate particles to be reinforced in the concrete source bin, mortar source bin and brick and tile source bin.

[0021] Preferably, in step S4, after adding homologous regenerated micro powder, a first-stage wet rolling shell formation is performed. After the first-stage wet rolling shell formation is completed, a silicate shell liquid is added, followed by a second-stage wet rolling shell formation. The silicate shell liquid is added in two stages. The amount of silicate shell liquid added in the first stage is 60% to 80% of the total amount of silicate shell liquid added. The second stage of silicate shell liquid is added after the first stage of silicate shell liquid is added, followed by intermittent rolling.

[0022] Preferably, in step S5, each carbonization cycle includes an air intake carbonization section and an air stop diffusion section; the re-wetting and settling between two adjacent carbonization cycles means that a re-wetting and settling section is set between two adjacent carbonization cycles, and the re-wetting and settling section uses atomized water to replenish the moisture of the wet shell aggregate.

[0023] Preferably, in step S5, the wet shell aggregate is weighed before the start of the first carbonization cycle to obtain the initial mass of the wet shell aggregate; when the difference in mass increment of the wet shell aggregate after the end of two adjacent carbonization cycles is less than 0.3% of the initial mass of the wet shell aggregate, and the change in the volume fraction of carbon dioxide in the carbonization tail gas is less than 0.5%, the intermittent carbon dioxide carbonization treatment is stopped.

[0024] Preferably, in step S6, the reinforced recycled aggregate with a retested water absorption rate higher than the upper limit of the preset target water absorption rate is marked as a batch with abnormal liquid absorption, the reinforced recycled aggregate with a retested crushing index higher than the upper limit of the preset target crushing index is marked as a batch with abnormal strength, and the reinforced recycled aggregate with a retested water absorption rate not higher than the upper limit of the preset target water absorption rate and a retested crushing index not higher than the upper limit of the preset target crushing index is marked as a qualified batch.

[0025] Preferably, batches with abnormal liquid absorption are subjected to silicate shell liquid replenishment spraying, wet rolling shell formation, and intermittent carbon dioxide carbonization treatment; batches with abnormal strength are subjected to calcium source filling liquid replenishment spraying, homologous regenerated micro powder replenishment, wet rolling shell formation, and intermittent carbon dioxide carbonization treatment.

[0026] Preferably, in step S6, when two consecutive batches are marked as abnormal liquid absorption batches, the amount of silicate shell liquid corresponding to the next batch of recycled aggregate to be reinforced is increased by 8% to 15% relative to the amount applied in the current batch; when two consecutive batches are marked as abnormal strength batches, the amount of calcium source filling liquid corresponding to the next batch of recycled aggregate to be reinforced is increased by 8% to 15% relative to the amount applied in the current batch, and the amount of homologous recycled micro powder corresponding to the next batch of recycled aggregate to be reinforced is increased by 5% to 12% relative to the amount applied in the current batch.

[0027] Preferably, steps S1 to S6 are performed by the construction waste recycled aggregate reinforcement processing line, which includes a compartment unit, an impregnation unit, a surface drainage unit, a spray feeding unit, a shelling unit, an intermittent carbonization unit, a retesting unit, and a batch update unit. The batch update unit updates the next batch feeding amount of the spray feeding unit and the shelling unit based on the attribute results of the batch with abnormal liquid absorption, batch with abnormal strength, or qualified batch output by the retesting unit.

[0028] Compared with existing technologies, the above technical solution has the following advantages:

[0029] I. This invention collects the area ratio of the attached old mortar layer and the fissure connectivity of recycled aggregate from construction waste, and determines the treatment level of the old mortar layer accordingly. This allows subsequent reinforcement treatment to match the residual degree of the old mortar layer and the fissure connectivity of the recycled aggregate from construction waste, avoiding fluctuations in treatment results caused by using uniform treatment conditions for recycled aggregate from different sources and with different degrees of damage. This is beneficial to improving the batch consistency of reinforced recycled aggregate.

[0030] Second, this invention uses a negative pressure introduction process with a calcium-containing pre-filled liquid to allow the pre-filled liquid to enter the pores and fissures of the regenerated aggregate to be reinforced. Then, by controlling the area ratio of the continuous liquid film region on the surface through surface drainage treatment, the calcium-containing liquid phase inside the pores is distinguished from the state of the aggregate surface, which is beneficial for the subsequent formation of a stable wet shell on the aggregate surface by the calcium source filling liquid, homologous regenerated micro powder and silicate shell liquid.

[0031] Third, the present invention uses homologous recycled micro powder to participate in wet rolling shell formation. The homologous recycled micro powder comes from the construction waste particles after compartmentation, which enables the shell material to correspond to the source composition of the recycled aggregate to be reinforced, reduces the compositional difference between the external powder and the old mortar layer, and improves the bonding stability between the shell and the surface of the recycled aggregate.

[0032] Fourth, the present invention employs intermittent carbon dioxide carbonization treatment with at least two carbonization cycles, and sets a re-wetting and static section between two adjacent carbonization cycles. At the same time, the difference in mass increment of wet shell aggregate and the change in carbon dioxide volume fraction in carbonization tail gas are used as stopping conditions, which enables the carbonization process to have a detectable and controllable termination basis, which is beneficial to improving the uniformity of carbonization treatment and process repeatability.

[0033] Fifth, after obtaining reinforced recycled aggregate, this invention retests the water absorption rate and crushing index, and updates the amount of calcium source filling liquid, homologous recycled micro powder, and silicate shell liquid for the next batch based on the attribute results of batches with abnormal liquid absorption, abnormal strength, or qualified batches. This allows for feedback correction of batch fluctuations in continuous production, thereby reducing the fluctuations in the retested water absorption rate and crushing index of reinforced recycled aggregate. Attached Figure Description

[0034] Figure 1 This is a schematic flowchart of the method for reinforcing lightweight building materials with recycled aggregates according to the present invention.

[0035] Figure 2 This is a schematic diagram of the old mortar layer treatment level determination and segmented spraying control logic of the present invention;

[0036] Figure 3 This is a schematic diagram of the abnormal batch dynamic feedback adjustment process of the present invention;

[0037] Figure 4 This is a schematic diagram of the cycle timing of the intermittent carbon dioxide carbonization process of the present invention;

[0038] Figure 5a This is a schematic cross-sectional view of the evolution of the microstructure of the recycled aggregate to be reinforced during the reinforcement process of the construction waste recycled aggregate of the present invention.

[0039] Figure 5bThis is a schematic cross-sectional view of the evolution of the microstructure of pretreated aggregates in the reinforcement process of the recycled aggregates from construction waste of the present invention.

[0040] Figure 5c This is a schematic cross-sectional view of the evolution of the microstructure of wet shell aggregate during the reinforcement process of the recycled aggregate from construction waste of the present invention.

[0041] Figure 5d This is a schematic cross-sectional view of the evolution of the microstructure of the recycled aggregate from construction waste during the reinforcement process of the present invention.

[0042] Figure 6 This is a schematic diagram showing the layout and pipeline routing of the construction waste recycled aggregate reinforcement processing line of the present invention;

[0043] Figure 7 This is a schematic diagram illustrating the image recognition of cracks in recycled aggregate to be reinforced after coloring and pre-wetting according to the present invention.

[0044] Figure 8 This is a schematic diagram illustrating the identification of a continuous liquid film region on the surface in an image containing water, as presented in this invention.

[0045] Figure 9a and Figure 9b This is a schematic diagram comparing the microstructure of recycled aggregate from construction waste before and after the enhancement treatment of this invention. Detailed Implementation

[0046] The following description, in conjunction with the accompanying drawings and specific embodiments, illustrates a method for reinforcing lightweight building materials using recycled aggregates. The method described in this embodiment is directly applied to the reinforcement treatment of recycled aggregates from construction waste. The treated material is the recycled aggregate to be reinforced, formed from waste concrete blocks, waste mortar blocks, and sintered brick and tile fragments from construction waste after impurity removal, crushing, and screening. The technical focus is on the treatment of the pores, old mortar layer, and surface shell of the recycled aggregate from construction waste.

[0047] In this embodiment, the raw materials processed originate from waste concrete blocks, waste mortar blocks, and sintered brick and tile fragments in construction waste. The construction waste is first subjected to manual and magnetic separation to remove reinforcing bars, wires, wood chips, plastic sheets, asphalt blocks, gypsum board fragments, and mud lumps. It is then crushed, screened, and air-separated, retaining particles with a diameter of 4.75mm to 16mm as the main particles for the recycled aggregate to be reinforced. To identify and utilize the differences in the source of the construction waste in subsequent processing, the crushed and screened construction waste particles are divided into concrete source bins, mortar source bins, and brick and tile source bins. Recycled aggregate particles and particles for preparing homologous recycled micro-powder are obtained from these bins respectively. The mass ratio of each source bin is determined by the weighing mass of the particles in the corresponding bin. The above processing corresponds to... Figure 1 The raw material pretreatment section and the storage section also correspond to Figure 6 The sub-warehouse units within.

[0048] Homogeneous recycled micro-powder is obtained by grinding and classifying particles used in homogeneous recycled micro-powder preparation. Specifically, particles from the mortar source bin are ground and sieved to obtain old mortar micro-powder with a particle size not exceeding 75 μm, and particles from the brick and tile source bin are ground and sieved to obtain brick and tile micro-powder with a particle size not exceeding 45 μm. The old mortar micro-powder and brick and tile micro-powder are mixed according to the mass ratio of the corresponding recycled aggregate particles to be reinforced in the concrete source bin, mortar source bin, and brick and tile source bin. For example, when a batch of recycled aggregate particles to be reinforced contains 35% mortar source bin particles and 20% brick and tile source bin particles, the old mortar micro-powder and brick and tile micro-powder are mixed at a mass ratio of 35:20. Using homogeneous recycled micro-powder allows the shelling material to match the source composition of the recycled aggregate from construction waste, reducing the compositional difference between the exogenous powder and the old mortar layer on the surface of the recycled aggregate from construction waste.

[0049] After the sorting is completed, initial testing is performed on the recycled aggregate to be reinforced. The testing indicators include initial water absorption rate, initial crushing index, apparent density, area ratio of the attached old mortar layer, and fracture connectivity. Initial water absorption rate is obtained through drying, soaking, surface drying, and weighing, with at least 5 kg of sample taken from each batch and three parallel samples. Initial crushing index is obtained through crushing tests, with three parallel samples taken from each batch. Apparent density is obtained through weighing and volumetric displacement methods. The area ratio of the attached old mortar layer is obtained through image recognition, and fracture connectivity is obtained through colored pre-wetting fracture images. Figure 7 The image shows a crack after pre-wetting with coloring, in which connected crack regions appear as continuously colored line regions, and non-connected crack regions appear as isolated line regions.

[0050] During image acquisition, the recycled aggregate particles to be reinforced are placed on a turntable for multi-angle imaging. At least three images are captured for each particle. A ring-shaped white light source is used for image acquisition, and a calibration ruler is set in the imaging area to establish the correspondence between pixel size and actual length. The acquired images undergo grayscale conversion, threshold segmentation, and binarization to identify the old mortar layer area, aggregate outer contour area, and crack area. The grayscale conversion, threshold segmentation, and binarization can be implemented using conventional image processing algorithms based on open-source computer vision libraries such as OpenCV. For example, Otsu's method is used for adaptive threshold segmentation to accurately extract boundary contours. Images from the same batch are processed using the same threshold rules. For areas with blurred boundaries, manual verification is used to correct the identification boundaries. The average value of the identification results from multiple angles is taken as the proportion of the attached old mortar layer area and the crack connectivity of the particle. At least 50 particles are detected in each batch, and their average value is taken as the detection value for that batch.

[0051] The area ratio of the attached old mortar layer is calculated according to the following formula:

[0052]

[0053] In the formula, This indicates the percentage of the area covered by the old mortar layer, expressed in % (%). This represents the projected area of ​​the region identified as the old mortar layer in the crack image, in mm². This represents the projected area of ​​the outer contour of the recycled aggregate particles to be reinforced, in mm². This area is calculated from the pixel area in the binarized image.

[0054] The fissure connectivity is calculated using the following formula:

[0055]

[0056] In the formula, Indicates the degree of fracture connectivity; This represents the length of a connected fracture in the fracture image, in mm. This represents the total length of the cracks in the crack image, in mm. The length of a connected crack is obtained by summing the lengths of the crack segments that are continuously connected by the dye, and the total length of the crack is obtained by summing the lengths of all identifiable crack segments.

[0057] The treatment levels for old mortar layers include Level 1, Level 2, and Level 3. Level 1 treatment is defined as follows: when the area of ​​the attached old mortar layer is not less than 45% and the crack connectivity is not less than 0.35; Level 3 treatment is defined as follows: when the area of ​​the attached old mortar layer is less than 25% and the crack connectivity is less than 0.18; all other cases are defined as Level 2 treatment. Figure 2 The logic for determining the treatment level of the old mortar layer is shown. Level 1 treatment corresponds to recycled aggregate to be reinforced with a large amount of residual old mortar layer and a high degree of crack connectivity; Level 3 treatment corresponds to recycled aggregate to be reinforced with a small amount of residual old mortar layer and a low degree of crack connectivity; Level 2 treatment corresponds to recycled aggregate to be reinforced that falls between the two.

[0058] Table 1 presents the initial test results of four batches of recycled aggregate from construction waste and the results of the old mortar layer treatment level determination.

[0059] Table 1. Parameter Information for Each Batch of Construction Waste

[0060] Batch A 45 35 20 9.8 26.5 2180 52 0.42 Level 1 processing Batch B 60 25 15 7.1 22.4 2260 36 0.26 Level 2 processing Batch C 75 15 10 5.2 18.3 2380 18 0.12 Level 3 processing Batch D 35 25 40 10.5 28.1 2110 48 0.38 Level 1 processing

[0061] As shown in Table 1, recycled aggregates from different sources of construction waste differ in terms of the proportion of the attached old mortar layer area, crack connectivity, initial water absorption rate, and initial crushing index. Therefore, applying treatment conditions corresponding to the treatment level of the old mortar layer to different batches can reduce the fluctuation of retested indexes caused by uniform treatment conditions.

[0062] In this embodiment, the calcium-containing endoplasmic pre-filling solution is introduced under negative pressure to reinforce the recycled aggregate. The calcium-containing endoplasmic pre-filling solution is a calcium-containing liquid that does not contain silicate film-forming components. In one embodiment, the calcium-containing endoplasmic pre-filling solution consists of a calcium chloride solution with a mass fraction of 3.0% to 6.0% and a polycarboxylate dispersant with a mass fraction of 0.05% to 0.15%, with the balance being water, and a pH of 6.5 to 8.5. In another embodiment, the calcium-containing endoplasmic pre-filling solution consists of a calcium acetate solution with a mass fraction of 2.0% to 4.0% and a polycarboxylate dispersant with a mass fraction of 0.05% to 0.10%, with the balance being water, and a pH of 6.5 to 8.5. The calcium-containing endoplasmic pre-filling solution can also be a calcium salt solution capable of providing water-soluble calcium ions and not forming silicate gels in a stored state, with a water-soluble calcium ion concentration of 0.15 mol / L to 0.60 mol / L.

[0063] In specific operation, the recycled aggregate to be reinforced is placed in the impregnation chamber. The impregnation chamber is pumped to a negative pressure state of -60kPa to -85kPa, and then calcium-containing pore pre-filling liquid is added. The negative pressure state is maintained for 5 to 12 minutes, and then restored to normal pressure state for 2 to 5 minutes, so that the calcium-containing pore pre-filling liquid enters the pores of the recycled aggregate to be reinforced. Then, the free calcium-containing pore pre-filling liquid that has not entered the pores of the recycled aggregate to be reinforced is discharged. Figure 5a The recycled aggregate to be reinforced is shown. Figure 5b The state of the calcium-containing pore pre-filled liquid after entering the pores and cracks of the old mortar layer is shown. Figure 6 The immersion unit is connected to a vacuum pump via a negative pressure extraction pipeline and to a calcium-containing internal pore pre-filled liquid storage tank via a liquid delivery pipeline.

[0064] After the negative pressure introduction of the calcium-containing pore pre-filled liquid, the surface drainage treatment is performed on the regenerated aggregate to be reinforced. The surface drainage treatment is carried out by a rolling purging method, with a drum speed of 8 to 18 r / min, a purging airflow velocity of 2 to 6 m / s, and a purging time of 1 to 4 min. During the purging process, the area ratio of the continuous liquid film region on the surface is identified by surface moisture content images. Image acquisition uses a fixed light source and a fixed shooting distance, with images acquired every 30 s; the continuous liquid film region appears as a continuous bright area in the surface moisture content image, while discontinuous wet areas are not included in the continuous liquid film region. When the area ratio of the continuous liquid film region on the surface is less than 5%, the surface drainage treatment is stopped, resulting in pretreated aggregate with calcium-containing pore pre-filled liquid retained in the pores and the area ratio of the continuous liquid film region on the surface being less than 5%. Figure 8 The image recognition effect of surface water content is shown, where the continuous bright area is the continuous liquid film area on the surface.

[0065] The area ratio of the continuous liquid film region on the surface is calculated according to the following formula:

[0066]

[0067] In the formula, This represents the percentage of the surface continuous liquid film area, expressed in % (%). This represents the area of ​​the region identified as a continuous liquid film in the surface water content image, in mm². The surface water content image represents the total visible surface area of ​​the recycled aggregate particles to be reinforced, in mm². After the surface drainage treatment, the pretreated aggregate still retains calcium-containing pre-filled liquid in the pores, while the particle surface does not retain a continuous liquid film.

[0068] Subsequently, according to the treatment grade of the old mortar layer, calcium source filling liquid, homologous regenerated micro powder, and silicate shell liquid are added to the pretreated aggregate, and wet rolling is performed to form a shell. The calcium source filling liquid can be a calcium hydroxide suspension with a mass fraction of 4.0% to 8.0%, or a calcium nitrate solution with a mass fraction of 3.0% to 6.0%; the calcium hydroxide suspension is stirred until it is in a uniform suspension state before use. The silicate shell liquid can be a sodium silicate solution with a modulus of 2.4 to 3.2 and a solid content of 6.0% to 12.0%, or a diluted potassium silicate solution.

[0069] The basic dosage of calcium source filling solution, homologous regenerated micro powder, and silicate shell liquid can be determined according to the treatment level of the old mortar layer of the aggregate to be reinforced. Based on the quality of the aggregate to be reinforced, the basic dosage of calcium source filling solution for the first treatment level is 28 mL / kg to 40 mL / kg, the basic dosage of homologous regenerated micro powder is 35 g / kg to 55 g / kg, and the basic dosage of silicate shell liquid is 20 mL / kg to 32 mL / kg; for the second treatment level, the basic dosage of calcium source filling solution is 22 mL / kg to 32 mL / kg, the basic dosage of homologous regenerated micro powder is 25 g / kg to 40 g / kg, and the basic dosage of silicate shell liquid is 16 mL / kg to 26 mL / kg; for the third treatment level, the basic dosage of calcium source filling solution is 18 mL / kg to 26 mL / kg, the basic dosage of homologous regenerated micro powder is 15 g / kg to 30 g / kg, and the basic dosage of silicate shell liquid is 12 mL / kg to 20 mL / kg. The above-mentioned basic dosage is used to determine the amount of material to be fed during the first treatment of the current batch; when updating the dosage for the next batch, it is increased based on the basic dosage corresponding to the old mortar layer treatment level. The calcium source filling liquid and silicate shell liquid are added in stages so that the calcium source filling liquid first adapts to the distribution state of the calcium-containing internal pores on the surface and in the pores of the pretreated aggregate, and then the homologous regenerated micro powder and silicate shell liquid form a wet shell layer.

[0070] In one embodiment, the calcium source filling solution is added using a segmented spraying method, which includes a first spray, intermittent rolling, and a second spray. The amount of calcium source filling solution used in the first spray is 18 mL / kg to 30 mL / kg based on the mass of the regenerated aggregate to be reinforced. For pretreated aggregate of Grade I treatment, the amount of calcium source filling solution used in the second spray is 40% to 70% of the amount used in the first spray; for pretreated aggregate of Grade II treatment, the amount of calcium source filling solution used in the second spray is 15% to 35% of the amount used in the first spray; for pretreated aggregate of Grade III treatment, the second spray is omitted. The intermittent rolling time is 2 min to 5 min. Figure 2 The segmented spray control logic corresponding to different treatment levels of old mortar layers is shown.

[0071] After adding the calcium source filling liquid, homologous regenerated micro powder is added, and the first stage of wet rolling shell formation is performed. The rolling time for the first stage of wet rolling shell formation is 3 to 8 minutes, and the roller inclination angle is 3° to 8°. After the first stage of wet rolling shell formation, silicate shell liquid is added, followed by the second stage of wet rolling shell formation. The silicate shell liquid is added in two stages. The first stage of silicate shell liquid accounts for 60% to 80% of the total silicate shell liquid added, and the second stage of silicate shell liquid is added after the first stage of silicate shell liquid is added, followed by intermittent rolling. The rolling time for the second stage of wet rolling shell formation is 4 to 10 minutes. After the above treatment, homologous regenerated micro powder, calcium source filling liquid, and silicate shell liquid form a wet shell layer on the outer surface of the pretreated aggregate, resulting in wet shell aggregate. Figure 5c The cross-sectional state of the aggregate after the formation of the wet shell is shown.

[0072] Subsequently, the wet shell aggregate undergoes intermittent carbon dioxide carbonization treatment for at least two carbonization cycles, with a re-humidification and settling period between adjacent carbonization cycles. Each carbonization cycle includes an air-intake carbonization section and an air-stop diffusion section, with a re-humidification and settling period between adjacent carbonization cycles. In the air-intake carbonization section, the carbon dioxide volume fraction is 20% to 40%, the carbonization chamber temperature is 20°C to 35°C, the relative humidity is 60% to 80%, and the air intake time is 10 to 25 minutes. In the air-stop diffusion section, the carbon dioxide intake valve is closed and the carbonization chamber is kept sealed, with an air-stop diffusion time of 5 to 15 minutes. In the re-humidification and settling period, the wet shell aggregate is moistened with atomized water, with a moistening amount of 0.5% to 1.5% of the wet shell aggregate mass, and the re-humidification and settling time is 8 to 20 minutes. Figure 4 The temporal relationship between carbon dioxide volume fraction, intake valve status, and water supply valve status is shown.

[0073] Before the start of the first carbonization cycle, the wet hull aggregate was weighed to obtain its initial mass. After each of the two adjacent carbonization cycles, the wet hull aggregate was weighed again, and the change in the volume fraction of carbon dioxide in the carbonization exhaust gas was measured. When the difference in the mass increment of the wet hull aggregate after the end of two adjacent carbonization cycles was less than 0.3% of the initial mass of the wet hull aggregate, and the change in the volume fraction of carbon dioxide in the carbonization exhaust gas was less than 0.5%, the intermittent carbon dioxide carbonization treatment was stopped, and reinforced recycled aggregate was obtained.

[0074] The difference in mass increment of wet hull aggregate is calculated using the following formula:

[0075]

[0076] In the formula, This represents the difference in mass increment of wet hull aggregate, in kg. This indicates the initial mass of wet hull aggregate, in kg. This represents the mass of wet shell aggregate after the i-th carbonization cycle, in kg. This represents the mass of wet shell aggregate after the (i-1)th carbonization cycle, in kg; i is an integer not less than 2.

[0077] The change in the volume fraction of carbon dioxide in the carbonized exhaust gas is calculated using the following formula:

[0078]

[0079] In the formula, This represents the change in the volume fraction of carbon dioxide in the carbonized exhaust gas, expressed in % (%). This represents the volume fraction of carbon dioxide in the carbonization exhaust gas at the end of the i-th carbonization cycle, expressed as % . This represents the volume fraction of carbon dioxide in the carbonization tail gas at the end of the (i-1)th carbonization cycle, in units of . Figure 5d The cross-sectional state of the reinforced recycled aggregate after intermittent carbon dioxide carbonization treatment is shown.

[0080] After obtaining the reinforced recycled aggregate, the water absorption rate and crushing index of the reinforced recycled aggregate are retested. Reinforced recycled aggregate with a retested water absorption rate exceeding the preset target upper limit is marked as a batch with abnormal liquid absorption; reinforced recycled aggregate with a retested crushing index exceeding the preset target upper limit is marked as a batch with abnormal strength; and reinforced recycled aggregate with a retested water absorption rate and a retested crushing index not exceeding the preset target upper limit is marked as a qualified batch. The preset target upper limit for water absorption rate can be set to 6.2%, and the preset target upper limit for crushing index can be set to 18.5%. Under different lightweight building material production conditions, the preset target upper limits for water absorption rate and crushing index can also be set according to the raw material grade, product strength grade, and production control standards.

[0081] When reinforced recycled aggregate is marked as having abnormal liquid absorption, the following treatments are performed: silicate shell liquid replenishment, wet rolling shell forming, and intermittent carbon dioxide carbonization. The amount of silicate shell liquid replenished is 10% to 20% of the original silicate shell liquid used in that batch. When reinforced recycled aggregate is marked as having abnormal strength, the following treatments are performed: calcium source filler liquid replenishment, homologous recycled micro powder addition, wet rolling shell forming, and intermittent carbon dioxide carbonization. The amount of calcium source filler liquid replenished is 10% to 20% of the original calcium source filler liquid used in that batch, and the amount of homologous recycled micro powder added is 5% to 15% of the original homologous recycled micro powder used in that batch. Figure 3 The process for handling the above-mentioned abnormal batches and updating the usage for the next batch is shown.

[0082] Furthermore, when two consecutive batches are marked as having abnormal liquid absorption, the amount of silicate shell liquid used in the next batch of recycled aggregate to be reinforced is increased by 8% to 15% compared to the amount used in the current batch. When two consecutive batches are marked as having abnormal strength, the amount of calcium source filling liquid used in the next batch of recycled aggregate to be reinforced is increased by 8% to 15% compared to the amount used in the current batch, and the amount of homologous recycled micro powder used in the next batch of recycled aggregate to be reinforced is increased by 5% to 12% compared to the amount used in the current batch. The above-mentioned method of updating the amount used in the next batch allows the reinforcement treatment of recycled aggregate from construction waste to be adjusted based on the retest results during continuous production.

[0083] In industrial implementation, the above steps are performed by a construction waste recycled aggregate reinforcement processing line. This line includes a compartmentation unit, an impregnation unit, a surface drainage unit, a spray feeding unit, a shelling unit, an intermittent carbonization unit, a retesting unit, and a batch renewal unit. The sorting unit is used to sort construction waste particles into concrete source bins, mortar source bins, and brick and tile source bins; the impregnation unit is used for negative pressure introduction treatment of calcium-containing internal pore pre-filling liquid; the surface drainage unit is used for rolling purging and surface moisture image acquisition; the spray feeding unit is used to add calcium source filling liquid, homologous regenerated micro powder, and silicate shell liquid to the pretreated aggregate; the shell forming unit is used for wet rolling shell forming; the intermittent carbonization unit is used for time sequence control of the air intake carbonization section, the air stop diffusion section, and the re-wetting static section; the retesting unit is used to retest the water absorption rate and retest the crushing index; the batch update unit updates the next batch feeding amount of the spray feeding unit and the shell forming unit according to the attribute results of abnormal liquid absorption batches, abnormal strength batches, or qualified batches output by the retesting unit. Figure 6 The layout and pipeline routing of the construction waste recycled aggregate reinforcement processing line are shown. The negative pressure exhaust pipeline is connected to the impregnation unit, the carbon dioxide intake pipeline is connected to the intermittent carbonization unit, the chemical spraying pipeline is connected to the spraying and feeding unit, and the atomizing humidification pipeline is connected to the intermittent carbonization unit.

[0084] To verify the treatment effect of the above method, a comparative test was conducted on batch A of recycled construction waste aggregate. Example 1 used the complete process described above; Comparative Example 1 used a unified calcium salt spraying and atmospheric pressure carbon dioxide carbonization treatment method; Comparative Example 2 used a treatment process basically the same as Example 1, but omitted surface drainage treatment, ensuring that the area of ​​the continuous liquid film region on the surface before entering the shell-forming stage accounted for more than 12%; Comparative Example 3 used a treatment process basically the same as Example 1, but replaced the homologous recycled micro powder with ordinary fly ash micro powder. Five parallel batches were set up in each group. The retested water absorption rate, water absorption rate reduction, retested crushing index, and crushing index reduction in Table 2 are all average values ​​of the five parallel batches. The batch variation coefficient of the retested water absorption rate was calculated from the retested water absorption rate of the five parallel batches. The test results are shown in Table 2.

[0085] Table 2. Test data on aggregate treatment effect

[0086] Example 1 Complete process processing 5.8 40.8 17.6 33.6 3.4 Comparative Example 1 Unified calcium salt spraying and atmospheric pressure carbon dioxide carbonization treatment 7.4 24.5 22 17 8.1 Comparative Example 2 Omit surface drainage treatment 6.9 29.6 21.2 20 7.5 Comparative Example 3 Homogeneous recycled micro powder replaced with ordinary fly ash micro powder 6.6 32.7 20.4 23 6.8

[0087] The decrease in water absorption rate is calculated using the following formula:

[0088]

[0089] In the formula, This indicates the decrease in water absorption rate, expressed in % (%). This indicates the initial water absorption rate, expressed in % (%). This indicates the water absorption rate after retesting, expressed in percent (%).

[0090] The decrease in crushing index is calculated using the following formula:

[0091]

[0092] In the formula, This indicates the decrease in crushing index, expressed in % %. This indicates the initial crushing index, expressed in % (%). This indicates the retested crushing index, expressed in percent.

[0093] The batch variation coefficient of water absorption rate in the retest is calculated according to the following formula:

[0094]

[0095] In the formula, This represents the batch variation coefficient of water absorption rate measured in retests, expressed in % %. This represents the standard deviation of water absorption rate from 5 parallel small batches, expressed in % . This represents the average water absorption rate from five parallel small-batch retests, expressed in percent.

[0096] Taking batch A as an example, the initial water absorption rate was 9.8%, and the retested water absorption rate after treatment in Example 1 was 5.8%. Therefore, the decrease in water absorption rate is:

[0097]

[0098] The initial crushing index of batch A was 26.5%, and the retested crushing index after treatment in Example 1 was 17.6%. Therefore, the decrease in crushing index is:

[0099]

[0100] As shown in Table 2, compared with the uniform calcium salt spraying and atmospheric pressure carbon dioxide carbonization treatment, the retested water absorption rate and retested crushing index of Example 1 were both lower; compared with the method of omitting surface drainage treatment, the batch variation coefficient of the retested water absorption rate of Example 1 was lower; compared with the method of replacing homologous recycled powder with ordinary fly ash powder, Example 1 also had lower values ​​in terms of retested water absorption rate and retested crushing index. Figure 9a (Porosity and crack areas of the old mortar layer) and Figure 9b Scanning electron microscopy (SEM) observations of the shell and pore-filled areas were performed at magnifications ranging from 1000x to 3000x. At least five aggregates were randomly selected from each group for observation in the old mortar layer area of ​​the cross-section. Samples were observed after drying, cross-section fixation, and gold sputtering. Before reinforcement treatment, pores and cracks in the old mortar layer were visible on the aggregate surface; after reinforcement treatment, the shell and pore-filled areas were visible on the aggregate surface.

[0101] To illustrate the batch update process, continuous production was tracked with a preset target upper limit for water absorption rate of 6.2% and a preset target upper limit for crushing index of 18.5%. The dynamic adjustment results for batches 10 to 13 are shown in Table 3.

[0102] Table 3 Batch Testing and Processing Information

[0103] Batch 10 6 18.2 qualified batches no No adjustment Achieve the preset target range Batch 11 6.7 18.4 Abnormal batch of liquid absorption no No adjustment is made; record one instance of abnormal aspiration. No continuous abnormal adjustment was triggered Batch 12 6.8 18.1 Abnormal batch of liquid absorption no No adjustment was made; two consecutive abnormal aspirations were recorded. Triggering the 13th batch of adjustments Batch 13 6.1 18 qualified batches yes The amount of silicate shell liquid used increased by 10% compared to batch 12. Return to the preset target range

[0104] As shown in Table 3, when batches 11 and 12 were consecutively marked as batches with abnormal liquid absorption, the amount of silicate shell liquid used in batch 13 increased by 10% compared to batch 12. The retested water absorption rate of batch 13 was lower than the upper limit of the preset target water absorption rate, and the retested crushing index of batch 13 was also lower than the upper limit of the preset target crushing index. These results indicate that retesting and updating the dosage for the next batch can be used to correct batch fluctuations in continuous production.

[0105] In summary, this embodiment focuses on the differences in the adhesion degree and crack connectivity of the old mortar layer in recycled construction waste aggregate. First, batch differences are identified through compartmentalization, initial testing, and determination of the old mortar layer treatment level. Then, the recycled construction waste aggregate is reinforced through a series of processes: negative pressure introduction of calcium-containing internal pore pre-filled liquid, surface drainage treatment, wet rolling shell formation of homologous recycled micropowder and silicate shell liquid, intermittent carbon dioxide carbonization treatment, and updating the dosage for the next batch after retesting. As can be seen from the retested water absorption rate, retested crushing index, and batch variation coefficient of retested water absorption rate in Table 2, and the continuous batch data in Table 3, this treatment method can reduce the retested water absorption rate and retested crushing index of the reinforced recycled aggregate, and reduce the fluctuation of retested water absorption rate in continuous batches.

[0106] It should be noted that the embodiments of the present invention have better implementability and are not intended to limit the present invention in any way. Any person skilled in the art may use the above-disclosed technical content to change or modify it into equivalent effective embodiments. However, any modifications or equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A method for reinforcing lightweight building materials with recycled aggregate, characterized in that, Includes the following steps: S1. Remove impurities, crush, screen and separate waste concrete blocks, waste mortar blocks and sintered brick and tile fragments from construction waste to obtain recycled aggregate to be reinforced, and prepare homologous recycled micro powder from the separated construction waste particles. S2. Collect the initial water absorption rate, initial crushing index, apparent density, area ratio of the attached old mortar layer, and fissure connectivity of the recycled aggregate to be reinforced, and determine the treatment level of the old mortar layer based on the area ratio of the attached old mortar layer and the fissure connectivity. S3. The calcium-containing pre-filled liquid is introduced into the recycled aggregate to be reinforced under negative pressure, and then the surface is drained to obtain pre-treated aggregate with calcium-containing pre-filled liquid in the pores and the area of ​​the continuous liquid film on the surface is less than 5%. S4. According to the treatment grade of the old mortar layer, calcium source filling liquid, homologous regenerated micro powder and silicate shell liquid are added to the pretreated aggregate in sequence, and wet rolling shell is performed to obtain wet shell aggregate; S5. The wet shell aggregate is subjected to intermittent carbon dioxide carbonization treatment for at least two carbonization cycles, and is allowed to stand for rehydration between two adjacent carbonization cycles to obtain reinforced recycled aggregate. S6. Retest the water absorption rate and crushing index of the reinforced recycled aggregate, and update the amount of calcium source filling liquid, homologous recycled micro powder and silicate shell liquid corresponding to the next batch of reinforced recycled aggregate based on the retest results.

2. The method for reinforcing lightweight building materials with recycled aggregate according to claim 1, characterized in that, In step S1, the construction waste is divided into a concrete source bin, a mortar source bin, and a brick and tile source bin, and the recycled aggregate particles to be reinforced and the particles for preparing homologous recycled micro powder are obtained from the concrete source bin, the mortar source bin, and the brick and tile source bin, respectively.

3. The method for reinforcing lightweight building materials with recycled aggregate according to claim 1, characterized in that, In step S2, the fracture connectivity is determined by the fracture image after coloring and pre-wetting, and the fracture connectivity is the ratio of the length of the connected fracture to the total length of the fracture.

4. The method for reinforcing lightweight building materials with recycled aggregate according to claim 3, characterized in that, In step S2, the treatment level of the old mortar layer includes Level 1, Level 2, and Level 3. When the area of ​​the attached old mortar layer is not less than 45% and the fissure connectivity is not less than 0.35, it is determined to be Level 1. When the area of ​​the attached old mortar layer is less than 25% and the fissure connectivity is less than 0.18, it is determined to be Level 3. All other cases are determined to be Level 2.

5. The method for reinforcing lightweight building materials with recycled aggregate according to claim 1, characterized in that, In step S3, the negative pressure introduction treatment of the calcium-containing pore pre-filling liquid includes placing the regenerated aggregate to be reinforced in an impregnation chamber, drawing the impregnation chamber to a negative pressure state and adding the calcium-containing pore pre-filling liquid, maintaining the negative pressure state and then restoring it to a normal pressure state, and discharging the free calcium-containing pore pre-filling liquid that has not entered the pores of the regenerated aggregate to be reinforced.

6. The method for reinforcing lightweight building materials with recycled aggregate according to claim 5, characterized in that, In step S3, the surface drainage treatment includes rolling and blowing the recycled aggregate to be reinforced after the pre-filled calcium-containing pore liquid negative pressure introduction treatment is completed, and identifying the area ratio of the continuous liquid film region on the surface through surface water content image.

7. The method for reinforcing lightweight building materials with recycled aggregate according to claim 4, characterized in that, In step S4, the calcium source filling liquid is added using a segmented spraying method, which includes a first spray, intermittent rolling, and a second spray. When the old mortar layer treatment level is Grade I, the amount of calcium source filling liquid used in the second spray is 40% to 70% of the amount used in the first spray. When the old mortar layer treatment level is Grade II, the amount of calcium source filling liquid used in the second spray is 15% to 35% of the amount used in the first spray. When the old mortar layer treatment level is Grade III, the second spray is omitted.

8. The method for reinforcing lightweight building materials with recycled aggregate according to claim 2, characterized in that, In step S1, the homologous recycled micro powder is obtained by grinding and classifying the homologous recycled micro powder preparation particles. The homologous recycled micro powder includes old mortar micro powder with a particle size of no more than 75 μm and brick and tile micro powder with a particle size of no more than 45 μm. The old mortar micro powder and the brick and tile micro powder are formulated according to the mass ratio of the corresponding recycled aggregate particles to be reinforced in the concrete source bin, the mortar source bin and the brick and tile source bin.

9. The method for reinforcing lightweight building materials with recycled aggregate according to claim 8, characterized in that, In step S4, after adding the homologous regenerated micro powder, a first-stage wet rolling shell formation is performed. After the first-stage wet rolling shell formation is completed, the silicate shell liquid is added, followed by a second-stage wet rolling shell formation. The silicate shell liquid is added in two stages. The amount of silicate shell liquid added in the first stage is 60% to 80% of the total amount of silicate shell liquid added. The second stage of silicate shell liquid is added after the first stage of silicate shell liquid is added, followed by intermittent rolling.

10. The method for reinforcing lightweight building materials with recycled aggregate according to claim 1, characterized in that, In step S5, each carbonization cycle includes an intake carbonization section and an exhaust diffusion section; the re-wetting and settling between two adjacent carbonization cycles refers to setting a re-wetting and settling section between two adjacent carbonization cycles, wherein the re-wetting and settling section uses atomized water to replenish moisture to the wet shell aggregate.

Citation Information

Patent Citations

  • Method for reinforcing recycled concrete fine aggregate by using carbon dioxide

    CN105174766A